2010
DOI: 10.1101/gr.100677.109
|View full text |Cite
|
Sign up to set email alerts
|

Deep RNA sequencing at single base-pair resolution reveals high complexity of the rice transcriptome

Abstract: Understanding the dynamics of eukaryotic transcriptome is essential for studying the complexity of transcriptional regulation and its impact on phenotype. However, comprehensive studies of transcriptomes at single base resolution are rare, even for modern organisms, and lacking for rice. Here, we present the first transcriptome atlas for eight organs of cultivated rice. Using high-throughput paired-end RNA-seq, we unambiguously detected transcripts expressing at an extremely low level, as well as a substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
364
9
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(409 citation statements)
references
References 48 publications
29
364
9
7
Order By: Relevance
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
See 2 more Smart Citations
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
“…Previous studies have shown that NTRs have fewer and shorter exons, less protein-coding potential, and less tissue-specific expression than annotated protein-coding genes (Bruno et al, 2010;Lu et al, 2010;Wetterbom et al, 2010;Zhang et al, 2010;Aanes et al, 2011;Graveley et al, 2011). To determine whether endospermic and embryonic NTRs have similar features, we analyzed the structure, coding potentials, and expression levels of the NTRs.…”
Section: Discovery Of Ntrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human, 95% of all intron-containing genes were estimated to be affected by AS (Pan et al, 2008), and recent comprehensive transcriptome analyses based on deep sequencing data revealed a wide extent of AS in plants as well (Filichkin et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012). Applying high-throughput RNA sequencing (RNA-seq) techniques, 42 to 61% of all multiexon genes from Arabidopsis thaliana (Filichkin et al, 2010;Marquez et al, 2012) and 33 to 48% of all rice (Oryza sativa) genes Zhang et al, 2010) were found to be associated with AS events. Despite its wide distribution and its huge regulatory potential, many fundamental questions, in particular concerning the control of AS decisions as well as the biological implications of the vast majority of events, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing platforms, such as the Illumina/Solexa Genome Analyzer, GS FLX Titanium System and ABI/SOLiD Gene Sequencer, can sequence in parallel massive amounts of cDNAs [10]. They have been successfully used to investigate the transcriptomes of a wide range of organisms including Pseudosciaena crocea, zebrafish, Aspergillus oryzae, rice, mouse and human [11][12][13][14][15][16]. The next-generation sequencing technologies have also been used in other functional genomics researches including genome annotation, small ncRNA profiling and aberrant transcript detection, which are areas previously covered by microarrays [17].…”
mentioning
confidence: 99%